Access to and Quality of Healthcare for Pregnant and Postpartum Women During the COVID-19 Pandemic - Brislane, Áine; Larkin, Fionnuala; Jones, Helen; Davenport, Margie H. (Frontiers in Global Women's Health, 2021)
Introduction: During the COVID-19 pandemic, obstetric care has adopted new precautions to ensure services can be maintained for pregnant women. The aim of this study was to describe access to and quality of obstetric care for pregnant and postpartum women during the COVID-19 pandemic and to identify factors that predict quality of care at this time. Methods: Between May 3 and June 28, 2020, we recruited women who were pregnant or within the first 6 months after delivery to participate in an online survey. This included questions on access to obstetric healthcare (type and place of health care provider, changes to obstetric appointments/services, appointment preferences) and the Quality of Prenatal Care Questionnaire (QPCQ). Results: Of the 917 eligible women, 612 (67%) were pregnant and 305 (33%) were in the first 6 months after delivery. Sixty-two percent (n = 571) reported that COVID-19 had affected their healthcare; appointments were rearranged, canceled or occurred via virtual means for 29% (n = 166), 29% (n = 167), and 31% (n = 175) of women, respectively. The majority preferred to physically attend appointments (74%; n = 676) and perceived the accompaniment of birth partners as important (77%; n = 471). Sixty-two percent (n = 380) were permitted a birth partner at delivery, 18% (n = 111) were unsure of the rules while 4% (n = 26) were not permitted accompaniment. During pregnancy, QPCQ was negatively associated with disruption to obstetric services including exclusion or uncertainty regarding birth partner permissions [F(7, 433) = 11.5, p < 0.001, R2 = 0.16] while QPCQ was negatively associated with inadequate breastfeeding support postpartum [F(1, 147) = 12.05, p = 0.001, R2 = 0.08]. Conclusion: Pregnant and postpartum have experienced disruption in their access to obstetric healthcare. Perceived quality of obstetric care was negatively influenced by cancellation of appointment(s), suspension of services and exclusion of birth partners at delivery. During this time, continuity of care can be fulfilled via virtual and/or phone appointments and women should receive clear guidance on changes to services including birth partner permissions to attend delivery.